Условия рудогенеза вольфрама в различных геологических средах - Воеводин, В.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
Experimental data accumulated up to this time allow one to revise and to expand notions on the tungsten ore genesis conditions and metallogeny. Besides the traditionally known industrial deposits associated with granitoid magmatism, it is possible to pick out the basaltofilling mineralization revealed in the structures of basite-ultrabasite magmatism. It is necessary to attract attention to the metamorphogenic mineralization (scheelite-bearing quartzites, skarnoides, tactites). By the example of foreign countries, its potential industrial significance is determined. All these genetically heterogeneous ore formations have different conditions and the mechanism of formation and are referred to many-type geotectonic structures.